A survey on modelling, control and challenges of stratospheric airships. (February 2022) - Zuo, Zongyu; Song, Jiawei; Zheng, Zewei; Han, Qing-Long
Abstract: The stratospheric airship, which is a new concept of autonomous atmospheric flight platforms, can operate over a period of time at very high altitudes to accomplish various military or commercial missions, such as monitoring, surveillance, and scientific exploration. The worldwide interest in stratospheric airships is still growing. However, modelling and control techniques for airships have fallen far behind those for fixed-wing aircraft. To show recent advances in modelling and control for stratospheric airships, this paper provides an insightful description of the related problems and a list of references for researchers and engineers focusing on this area. The literature is categorized according to major topics in this area: dynamic modelling, control design, and ascent/descent flight control. Moreover, an application of the path-following control with real-time flight test results is presented for an autonomous prototype airship. Finally, some challenging issues are addressed for future research.